Exploring the Role of Educational Policy Implementation in Reducing Urban–Rural Learning Disparities through Scholarship Programs - Sitti Nuralan; Arham Rahim; Ògúnléye, Michael Olá (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the role of educational policy implementation in reducing urban-rural learning disparities through scholarship programs. Educational disparities between urban and rural areas have persisted across many nations, affecting student outcomes due to differences in access to resources, infrastructure, and qualified teachers. Scholarship programs have emerged as an effective policy tool to address these gaps, providing financial support and enabling rural students to pursue higher education opportunities. This research examines the impact of scholarship policies on bridging the urban-rural education divide, focusing on the performance outcomes of scholarship recipients compared to non-recipients. The study also discusses the socio-economic barriers and challenges faced by rural students and evaluates how scholarships, along with additional support mechanisms such as mentorship and academic workshops, contribute to improving academic performance. The findings suggest that while scholarships have a significant positive effect on academic outcomes, a more comprehensive approach, including better infrastructure, teacher quality, and socio-emotional support, is necessary to fully address educational inequities. This research provides insights into how well-designed scholarship programs, embedded within broader educational reforms, can effectively reduce disparities in educational access and outcomes between urban and rural students.